Pharmacological management of allergic rhinitis: a consensus statement from the Malaysian society of allergy and immunology - Abdullah, Baharudin; Abdul Latiff, Amir Hamzah; Manuel, Anura Michelle; Mohamed Jamli, Faizah; Dalip Singh, Harvinder Singh; Ismail, Intan Hakimah; Jahendran, Jeevanan; Saniasiaya, Jeyasakthy; Kee Chen, Kent Woo; Khoo, Phaik Choo; Singh, Kuljit; Mohammad, Nurashikin; et al. (Taylor and Francis Group, 2022)
The goal of allergic rhinitis (AR) management is to achieve satisfactory symptom control to ensure good quality of life. Most patients with AR are currently treated with pharmacotherapy. However, knowledge gaps on the use of pharmacotherapy still exist among physicians, particularly in the primary care setting, despite the availability of guideline recommendations. Furthermore, it is common for physicians in the secondary care setting to express uncertainty regarding the use of new combination therapies like intranasal corticosteroid plus antihistamine combinations. Inadequate treatment leads to significant reduction of quality of life that affects daily activities at home, work, and school. With these concerns in mind, a practical consensus statement was developed to complement existing guidelines on the rational use of pharmacotherapy in both the primary and secondary care settings.